Isolation of Methicillin Resistant - Staphylococcus aureus in Midwifery Students Faculty of Medicine Universitas Padjadjaran September–December 2012 - Robinee Panirchelvam; Imam Megantara; Melati Sudiro (Althea Medical Journal, 2015)
Background: Methicillin Resistant-Staphylococcus aureus (MRSA) is resistant bacteria to certain types of beta-lactam antibiotics. Commonly, the MRSA infection is acquired in hospitals, long-term care facilities, or similar institutional settings. Mid-wives are one of the health professional that have a major risk to get MRSA infection and could lead the infection among patients. This research is aimed to identify MRSA among the midwifery studentsMethods: A descriptive study was conducted from September–December 2012 at the Microbiology laboratory to identify the proportion of MRSA among the mid-wife students from Faculty of Medicine, Universitas Padjadjaran. Twenty-five samples were chosen using simple random sampling based on their registration number. The inclusion criterias were healthy students, and 18 to 22 years old. Both nostrils were sampled with a sterile culture swab on both the subject’s nostrils. Gram staining was done in order to identify the gram positive bacteria, Staphylococcus aureus. The samples were inaculated in Mannitol salt agar (MSA), incubated for 24 hours and at 37 ̊ C. After 24 hours, catalase and coagulase tests were done. Moreover, for the susceptibility testing, the chosen media for this study was Mueller Hinton Agar (MHA) and with 30μg Cefoxitin disk. After incubation, the zone of inhibition of the colony less than ≤ 21mm was considered resistant to methicillin.Results: Colonization of MRSA was about 3 out from 25 samplesConclusions: The MRSA colonization in the anterior nasal does exist in midwife students, a further study with more samples should be conducted. [AMJ.2015;2(1):204–7]